2012
DOI: 10.1017/s0144686x12000530
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes from a peer tutor model for teaching technology to older adults

Abstract: A key component of social work ethics is social justice and equitable access to resources. Increasingly, this includes access to technology. This study addresses issues related to the 'digital divide' by testing a peer tutor model (Technology and Aging Project, TAP) to teach adults aged  and older how to use information and communication technologies (ICTs) such as email, the internet, online chat rooms and discussion groups, internet-based support groups, and voice technology and webcams. Participants from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 39 publications
(61 reference statements)
1
59
1
Order By: Relevance
“…Recently, it was suggested that ICT training through peer tutors is also effective. 33 This training model is considered to be appropriate because it highlights the role of trainers as caring and sensitive people, capable of bringing adequate support for older adults. It was reported that adequate training has a positive impact not only on older adults’ skill in technology use but also on their attitudes toward technology (less anxiety, more perceived usefulness, increased interest, and self-efficacy).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was suggested that ICT training through peer tutors is also effective. 33 This training model is considered to be appropriate because it highlights the role of trainers as caring and sensitive people, capable of bringing adequate support for older adults. It was reported that adequate training has a positive impact not only on older adults’ skill in technology use but also on their attitudes toward technology (less anxiety, more perceived usefulness, increased interest, and self-efficacy).…”
Section: Discussionmentioning
confidence: 99%
“…With no information, if you haven't got a computer, I mean I have but there's nothing on the computer like… (Emma, 62)Individuals expressed frustration that due to their lack of IT knowledge they are now unable to access the same volume of information they were once able to. Whilst our participants did not use the term ‘digital exclusion’ (Woodward et al 2013), it was clear that they experienced its effects.…”
Section: Resultsmentioning
confidence: 99%
“…Even though it is clear that older people, especially those from rural areas and lower socio-economic groups, are disadvantaged in relation to ICT uptake and use, there is a growing body of research that is examining ICT use by older people (Laganá et al 2011; Shapira, Barak and Gal 2007; Slegers, Van Boxtel and Jolles 2008; Sum et al 2008; Toler Woodward et al 2013; Warburton, Cowan and Bathgate 2013; Warburton et al 2013; Xie 2007). Research conducted by Shapira, Barak and Gal (2007), that examined the effects of ICT training on a group of elderly participants with a mean age of 80 (N = 20), found significant improvements in measures such as life satisfaction, depression, loneliness and self-control when compared with a control group that did not receive the training.…”
Section: Ageing and The Network Society In Rural Australiamentioning
confidence: 99%